Let the present age of son = x years then present age of man will be x+24 years

After 2 years, Age of son = x+2 years and age of man= x+24+2 yrs =x+6 years

According to given condition, x+26 = 2(x+2)

x+26= 2x+4

x=22 present age of his son =22 years and his father's present age=x+24= 46years

Let the present age of son be x Then age of father will be 24+x Son's age after 2 years = x+2 Father's age after 2 years = 24+x+2 = 26+x 26+x=2(x+2) 26+x=2x+4 26-4 =2x-x 22=x Therefore .... Present age of son = 22 years Present age of father = 22+24=46 yrs